2022
DOI: 10.6007/ijarbss/v12-i1/11637
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Social Entrepreneurship Approach in Enhancing Homepreneur Business Opportunities: The Conceptual Model

Abstract: The pandemic is a public health crisis with deep implications for society. The negative impacts of the Covid-19 pandemic are felt greater than the positive ones. This may cause the socioeconomic development in Malaysia to be more difficult. The purpose of this research is to explain the important role of social entrepreneurship factor, specifically focusing on human capital and social capital, in encouraging homepreneur business opportunities. The paper draws on the work of others to add conclusion from both d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…EI is regarded as a significant predictor since entrepreneurship is characterized as planned behavioral action and is viewed as an initial step that would lead to the formation of entrepreneurial venture. In Malaysia, several studies have been found focusing on various aspects of social entrepreneurship, review of concepts and meaning (Rahim and Mohtar, 2015;Ali and Suhaimi, 2016); practices (Suhaimi et al,, 2013); roles and impact of SE (Adnan et al, 2018;Said et al, 2015); participation and dimensions of SE (Othman and Wahid, 2014), however, a dearth literature was found to focus on understanding behavioural intention towards SE. Hence this paper aims to fill the gaps by contributing to the literature using the Social entrepreneurial orientation (SEO) framework introduce by proposed by Bingyan Tu et al This framework is drawn from the theory of Planned Behavior.…”
Section: Literature Reviewmentioning
confidence: 99%
“…EI is regarded as a significant predictor since entrepreneurship is characterized as planned behavioral action and is viewed as an initial step that would lead to the formation of entrepreneurial venture. In Malaysia, several studies have been found focusing on various aspects of social entrepreneurship, review of concepts and meaning (Rahim and Mohtar, 2015;Ali and Suhaimi, 2016); practices (Suhaimi et al,, 2013); roles and impact of SE (Adnan et al, 2018;Said et al, 2015); participation and dimensions of SE (Othman and Wahid, 2014), however, a dearth literature was found to focus on understanding behavioural intention towards SE. Hence this paper aims to fill the gaps by contributing to the literature using the Social entrepreneurial orientation (SEO) framework introduce by proposed by Bingyan Tu et al This framework is drawn from the theory of Planned Behavior.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Rahim et al (2022), the term homepreneur is new in Malaysia, and it refers to the entrepreneur who operates a small company or business from home. They manage their business and attract their target customer without investing more time in meeting them, using social media.…”
Section: Homepreneurmentioning
confidence: 99%
“…This situation can help entrepreneurs balance their family needs and business work (Kapasi & Gollaway, 2015). Additionally, safety issues like commuting to work or unsafe workplaces, particularly for women, are a reason for the development of homepreneurs (Rahim et al, 2022). Furthermore, due to the effects of post-COVID-19 on the economy and employment options, initiatives to raise family income are also contributing reasons for the growth of homepreneurs (Rahim et al, 2022).…”
Section: Homepreneurmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Peredo and McLean (2006), social entrepreneurs aim to build and increase social value by contributing to the welfare of their community. Businesses should be socially responsible and give back to the community by addressing critical societal requirements to encourage and provide a better and sustainable world (Rahim, Mohtar, 2015). Furthermore, in craftsmanship, the craftsman is closely related to his people rather than by common motives or gains.…”
Section: Introductionmentioning
confidence: 99%